Mapping Immigrant Children’s Ethnoracialized Identities in Canada: K–5 Muslim Students Share Stories with their Mothers - Oladi, Soudeh (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
This study investigates the schooling experiences of K–5 Muslim immigrant children to address the underexplored area of post-migration schooling within the Canadian context. Centered on the stories K–5 children share with their mothers, the study focuses on students’ identity formation, sense of belonging, and academic performance. Theoretically grounded in critical race theory and decolonial education as conceptual frameworks, the research explores the multi-dimensional experiences of immigrant children, moving beyond the monolithic narratives often enacted by dominant power structures. Utilizing a qualitative methodological approach, the study engages 10 Muslim-identifying mothers in semi-structured interviews, revealing insights about the role of mothers as knowledge holders and validating K–5 immigrant students’ schooling experiences. Findings indicate key themes including subtractive teacher practices, subversive allyship, racialization, marginalization, and the interplay of identity and religion. The study proposes targeted recommendations for school-based supports, teaching practice, and programs of teacher education to address post-migration schooling challenges.